Biomass from young hardwood stands on marginal lands: Allometric equations and sampling methods. (March 2017) - Lupi, Carlo; Larocque, Guy R.; DesRochers, Annie; Labrecque, Michel; Mosseler, Alex; Major, John; Beaulieu, Jean; Tremblay, Francine; Gordon, Andrew M.; Thomas, Barb R.; Vézina, André; Bouafif, Hassine; et al.
Abstract: We developed allometric equations for small-diameter woody species growing on mixed forest marginal lands, which are potential sources of biomass for bioenergy. Eleven species of trees and shrubs were sampled from a site located in eastern Canada. Equations derived in this study generally performed better than equations from the literature. Also, fixed-area plots (FAP) and line-intersect sampling (LIS) methods using both random or systematic selection of sampling units were compared to determine which method required the lowest number of measurements to estimate stand biomass for the same precision. The fixed-area plots method was successfully used to estimate relatively accurately oven-dry biomass per hectare. Results indicated that potentially harvestable woody biomass (oven dry basis) varied between 33-41 and 12–13 t ha −1 for the most and least productive marginal sites respectively. On the most productive site, LIS estimates (between 20 and 42 t ha −1 ) were usually lower than those obtained using different FAP sampling methods (i.e. systematic or random, small (50 m 2 ) or large (100 m 2 ) plots), but similar on the more open sites (between 10 and 14 t ha −1 ). Small FAP resulted in a plot without measurements in one case. Moreover, estimates based on small FAP were generally higher, even if not significantly different from larger plot estimates. We therefore suggest using FAP with 100 m 2 plots to estimate small-diameter woody biomass on marginal lands with dense vegetation, while LIS, even if promising for open stands, needs further evaluation before recommendation. Highlights: Development of new allometric equations for 11 small woody species on marginal lands. Comparison of sampling methods and estimation of harvestable biomass at the stand level. Fixed-area plots of 100 m 2 are recommended for young stands located on marginal lands. Further testing of line-intersect sampling and other methods is suggested.